2011
DOI: 10.1007/s10157-011-0545-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhibitors of renin–angiotensin–aldosterone system (RAS) and combination therapy of steroids plus RAS inhibitors for patients with advanced immunoglobulin A nephropathy and impaired renal function

Abstract: Combination therapy with steroids and RASIs was not superior to monotherapy with RASIs for advanced IgAN with impaired renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Several previous reports from various countries have facilitated a full understanding of the renoprotective effects of RASIs (11)(12)(13). Results from our laboratory have also demonstrated the beneficial effects of these medications, especially in patients with advanced IgAN with an impaired renal function (19)(20)(21), a condition for which fish oil therapies, including the omega-3 polyunsaturated fatty acids (PUFA) eicosapentaenoic acid and docosahexaenoic acid (DHA), are also beneficial, as reported by several groups (22)(23)(24)(25). In an elegant series of studies, Donadio and colleagues reported the short-and long-term beneficial effects of fish oil on IgAN using a randomized controlled trial.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Several previous reports from various countries have facilitated a full understanding of the renoprotective effects of RASIs (11)(12)(13). Results from our laboratory have also demonstrated the beneficial effects of these medications, especially in patients with advanced IgAN with an impaired renal function (19)(20)(21), a condition for which fish oil therapies, including the omega-3 polyunsaturated fatty acids (PUFA) eicosapentaenoic acid and docosahexaenoic acid (DHA), are also beneficial, as reported by several groups (22)(23)(24)(25). In an elegant series of studies, Donadio and colleagues reported the short-and long-term beneficial effects of fish oil on IgAN using a randomized controlled trial.…”
Section: Discussionsupporting
confidence: 56%
“…For example, the number of advanced cases involving T2 and T3 in the Oxford analysis tended to be higher in the DILAZEP group, and the ACEI/ARB ratio was also higher in the DI-LAZEP group. In our previous reports, we demonstrated the long-term beneficial effects of RASIs on the prevention of end-stage renal disease; however, we could not show any effects causing significant decreases in the levels of U-Prot in the advanced IgAN cases (20,21), and the decreases in the levels of U-Prot caused by ARBs were greater than those caused by ACEIs in these cases (19). In addition, we could not deny that these differences between the groups accounted for the lack of significant decreases in the levels of U-Prot in the DILAZEP group, although the ability of RASIs to decrease the levels of U-Prot is widely recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Although slowly progressive over decades, IgAN is not a benign disease. Since IgAN was first described over 40 years ago, patients with this disease have been treated with oral steroids [4] , [14] , [15] , steroid pulse therapy [5] , [6] , tonsillectomy [7] , [16] , [17] , renin-angiotensin aldosterone system inhibitors [18] [20] , eicosapentaenoic acid [21] , statins [22] and combinations of these agents [23] . Although these agents were found to improve short and intermediate term renal outcomes, less is known about very long term outcomes in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The other important mechanism of deterioration of renal function is caused by which aberrantly glycosylated serum IgA1 causes mesangial IgA deposition and inflammatory changes, such as crescent formation and endothelial hyper cellularity in the glomeruli [2]. This can be treated by steroid therapy to suppress inflammatory changes in the glomeruli and interstitium [8] (Table 2). IgAN patients with persistent proteinuria ≥ 1g/d, despite optimized supportive care, should be given a 6-month course of corticosteroids if GFR is above 50 ml/min.…”
Section: Corticosteroidsmentioning
confidence: 99%